AB1288 Prediction of amenorrhea in female rheumatoid arthritis patients with tripterygium wilfordii hook f. (12th June 2018) - Zhang, C.; Xu, Y.; Liu, M.; He, X.; Lu, C.; Lu, A.
Abstract : Background: The Chinese anti-inflammatory and immunosuppressive herbal remedy Tripterygium wilfordii Hook F (TwHF) is a widely used and effective treatment for rheumatoid arthritis (RA). Ovarian failure is one of the most important adverse effects among pre-menopausal women with TwHF therapy. Objectives: To construct a statistical model for pre-treatment prediction of amenorrhea after TwHF therapy. Methods: In this retrospective study, potential predictors of amenorrhea including demographic and clinical data were retrieved. Multivariate logistic regression models were used to evaluate the association between pre-treatment variables and amenorrhea. The probability of amenorrhea was calculated for combinations of pre-treatment variables. Results: Post-TwHF therapy amenorrhea rate was 10.9% (70 of 641). The mean age was 36.2±5.5 years, mean body mass index 22.5±7.5 kg/m2. Age was the strongest determinant of this adverse effect. In the final model, age >36 years, cumulative dose >4000 mg, and WBC<4.1 × 10^9/L, were predictive of amenorrhea with adjusted odds ratios of 1.7 for TwHF therapy vs disease modifying antirheumatic drug (95% CI, 1.2–3.2, p=0.017), 3.1 age >40 years (95% CI, 1.8–4.7, p<0.001), 2.8 cumulative dose >6000 mg (95% CI, 1.6–4.3, p<0.001), and 2.7 for WBC<3.5 × 10^9/L (95% CI, 1.4–6.3, p=0.012). The probability of amenorrhea can be as high as 76% or as low as 9% depending on the age, cumulative dose, WBC and the type of combination treatments employed. Conclusions: This is first study to identify pre-treatment factors predictive of amenorrhea following TwHF therapy. Our model allows for optimum patient counselling and will help clarify expectations for the probability of amenorrhea following TwHF therapy. Reference: [1] Chi Zhang, et al: Safety profiles of tripterygium wilfordii hook f: a systematic review and meta-analysis. Front. Pharmacol. 7:402, 2016. Acknowledgements: The study was supported by the National Natural Science Foundation of China (No. 81503449). Disclosure of Interest: None declared